Photocatalytic Application of Two-dimensional Materials-based Heterostructure Based on Molybdenum and Tungsten Disulfides and Gallium Nitride: A Density-Functional Theory Study. (December 2020) - Zulkifli, N.A.A; Said, S.M.; Taib, M.F.M.; Arifin, K.; Mahmood, S.M.; Woon, K.L.; Patel, Shobhit K.; Tan, C.L.; Zakaria, R.
Highlights: Based on density functional theory (DFG, MoS2 /GaN/MoS2, WS2 /GaN and WS2 /GaN/WS2 vdW heterostructures are the most appropriate for photocatalytic applications. The charge transfer from GaN to MoS2 or WS2 form a staggered gap which aids in exciton disassociation and charge separation. Studied models are expected to harvest UV to visible light with absorption coefficient up to 3.38 × 10 -5 cm -1 at wavelength of 102 nm. Proposed heterosystem as a promising device for various optoelectronic application specifically in from UV to near-infrared with high performance. Due to the high density of states contributed by MoS2 or WS2 layer, the addition of MoS2 or WS2 layer widened the bandgap while addition of GaN layer narrows the bandgap. Abstract: Photocatalytic water splitting is one of the methods to produce hydrogen fuel by reducing the water into the oxygen and hydrogen provided that the bandgap of one catalyst is larger than +1.23 eV. In this paper, based on density functional theory, we investigated the structural, electronic and optical properties of heterostructure MoS2 (WS2 ) paired with GaN and we found out that MoS2 /GaN/MoS2, WS2 /GaN and WS2 /GaN/WS2 vdW heterostructures are potential photocatalysts for photocatalytic applications. From the band structure and electronic partial density of states (PDOS), we confirm that all simulated heterostructures are direct semiconductors of type II band alignment with valence band maximum and conduction band minimum localized at pz orbital N atom of GaN and dz 2 orbital Mo (or W) atom of MoS2 and WS2 respectively. The band offset induced by efficient interlayer charge transfer form a staggered gap which aids in exciton disassociation and charge separation. Our studied models are expected to harvest UV to visible light with absorption coefficient up to 3.38 × 10 -5 cm -1 at wavelength of 102 nm. On top of that, our proposed heterosystem are also believed to be a promising device for various optoelectronic application specifically in from UV to near-infrared with high performance.